Midnight rider - Harlow, Joan Hiatt (M.K. McElderry Books, 2005)
In Boston in 1775, orphaned fourteen-year-old Hannah is indentured to the family of a British general and begins attending secret meetings disguised as a boy, then passing messages and warnings to the revolutionaries using her beloved horse Promise.